Advanced carbon dots via plasma-induced surface functionalization for fluorescent and bio-medical applications. Issue 26 (26th June 2017) - Park, So Young; Lee, Che Yoon; An, Ha-Rim; Kim, Hyeran; Lee, Young-Chul; Park, Edmond Changkyun; Chun, Hang-Suk; Yang, Hee Young; Choi, Sae-Hae; Kim, Hee Sik; Kang, Kyoung Suk; Park, Hyun Gyu; et al.
Abstract : AC-paints is a photo-luminescent and multifunctional carbon dot via atmospheric plasma treatment. We reported bioimaging and antibacterial reaction of AC-paints. Abstract : Multifunctional carbon-based nanodots (C-dots) are synthesized using atmospheric plasma treatments involving reactive gases (oxygen and nitrogen). Surface design was achieved through one-step plasma treatment of C-dots (AC-paints) from polyethylene glycol used as a precursor. These AC-paints show high fluorescence, low cytotoxicity and excellent cellular imaging capability. They exhibit bright fluorescence with a quantum yield twice of traditional C-dots. The cytotoxicity of AC-paints was tested on BEAS2B, THLE2, A549 and hep3B cell lines. The in vivo experiments further demonstrated the biocompatibility of AC-paints using zebrafish as a model, and imaging tests demonstrated that the AC-paints can be used as bio-labels (at a concentration of <5 mg mL −1 ). Particularly, the oxygen plasma-treated AC-paints (AC-paints-O) show antibacterial effects due to increased levels of reactive oxygen species (ROS) in AC-paints (at a concentration of >1 mg mL −1 ). AC-paints can effectively inhibit the growth of Escherichia coli ( E. coli ) and Acinetobacter baumannii ( A. baumannii ). Such remarkable performance of the AC-paints has important applications in the biomedical field and environmental systems.